Enolase From Aspergillus fumigatus Is a Moonlighting Protein That Binds the Human Plasma Complement Proteins Factor H, FHL-1, C4BP, and Plasminogen - Dasari, Prasad; Koleci, Naile; Shopova, Iordana A.; Wartenberg, Dirk; Beyersdorf, Niklas; Dietrich, Stefanie; Sahagún-Ruiz, Alfredo; Figge, Marc Thilo; Skerka, Christine; Brakhage, Axel A.; Zipfel, Peter F. (Frontiers in Immunology, 2019)
The opportunistic fungal pathogen Aspergillus fumigatus can cause severe infections, particularly in immunocompromised individuals. Upon infection, A. fumigatus faces the powerful and directly acting immune defence of the human host. The mechanisms how A. fumigatus evades innate immune attack and complement are still poorly understood. Here, we identify A. fumigatus enolase, AfEno1, which was also characterized as fungal allergen, as a surface ligand for human plasma complement regulators. AfEno1 binds Factor H, FHL-1, C4BP and plasminogen. Factor H attaches to AfEno1 via two regions, via SCRs6-7 and SCRs19-20, and FHL-1 contacts AfEno1 via SCRs 6-7. Both regulators when bound to AfEno1 retain cofactor activity and assist in C3b inactivation. Similarly, the classical pathway regulator C4BP binds to AfEno1, and bound to AfEno1, C4BP assists in C4b inactivation. Plasminogen which binds to AfEno1 via lysine residues is accessible for the activator tPA, and active plasmin cleaves the chromogenic substrate S2251, degrades fibrinogen, and inactivates C3 and C3b. Plasmin attached to swollen A. fumigatus conidia damages human A549 lung epithelial cells, reduces the cellular metabolic activity and induces cell retraction which results in exposure of the extracellular matrix. Thus A. fumigatus AfEno1 is a moonlighting protein and virulence factor which recruits several human regulators. The attached human regulators allow the fungal pathogen to control complement at the level of C3 and to damage endothelial cell layers and tissue components.